Optimasi Kadar Fenilbutazon dalam Pembawa Vesikular Etosom (Optimization of Concentration of Phenylbutazone in Ethosomes Vesicular Carrier) - Nur Illiyyin Akib; Muhammad Handoyo Sahumena; Yunita Dawu; Vica Aspadiah; Indria Hafizah; Halimahtussaddiyah Ritonga (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2020)
Background: Phenylbutazone is a class of non-steroidal anti-inflammatory drugs (NSAIDs) used in the treatment of rheumatoid arthritis. Phenylbutazone is used by the transdermal route to reduce the irritating effect on the gastrointestinal tract. Purpose: This study aims to obtain phenylbutazone suspensions with optimal levels in the ethosome vesicular carrier. Methods: Preparation was carried out by the hot method (40oC) and cold method (30oC) as well as variations in the concentration of phosphatidylcholine (2% and 3%) and ethanol (30%, 35%, and 40%). Characterization of vesicles, namely the shape and size of vesicles using optical microscopy and entrapment efficiency using the spectrophotometer method with λ maks 266.6 nm. Optimization of phenylbutazone levels was carried out at a concentration of 0.1%; 0.15%; 0.2%; and 0.25%. The optimum formula was obtained at a concentration of phosphatidylcholine 3% and ethanol 35% prepared by the hot method. Results:. The form of a Small Unilamellar Vesicle (SUV), a size of 23.7 nm, and entrapment efficiency is 88.358%. Optimization of phenylbutazone levels was obtained at a concentration of 0.1% with entrapment efficiency of 88.358%. Conclusion: The optimum level of phenylbutazone in the vesicular carrier ethosome was 0.1%.Keywords: ethosome, optimation, phenylbutazone, transdermal ABSTRAKLatar Belakang: Fenilbutazon merupakan golongan obat antiinflamasi non stroid (AINS) yang digunakan pada pengobatan penyakit rheumatoid arthritis. Fenilbutazon digunakan melalui rute transdermal untuk mengurangi efek iritasi pada saluran cerna. Tujuan: Penelitian ini bertujuan memperoleh suspensi fenilbutazon dengan kadar yang optimal dalam pembawa vesikular etosom. Metode: Preparasi dilakukan dengan metode panas (40oC) dan metode dingin (30oC) serta variasi konsentrasi fosfatidilkolin (2% dan 3%) dan etanol (30%, 35%, dan 40%). Karakterisasi vesikel yaitu bentuk dan ukuran vesikel menggunakan mikroskop optik serta efisiensi penjerapan menggunakan metode spektrofotometer pada λmaks 266,6 nm. Optimasi kadar fenilbutazon dilakukan pada konsentrasi 0,1%; 0,15%; 0,2%; dan 0,25%. Diperoleh formula optimum pada konsentrasi fosfatidilkolin 3% dan etanol 35% yang dipreparasi dengan metode panas Hasil: Vesikel yang diperoleh berbentuk Small Unilamellar Vesicle (SUV), ukuran 23,7 nm, dan efisiensi penjerapan 88,358%. Optimasi kadar fenilbutazon diperoleh pada konsentrasi 0,1% dengan efisiensi penjerapan 88,358%. Kesimpulan: Disimpulkan bahwa kadar optimum fenilbutazon dalam pembawa vesikular etosom adalah 0,1%.Kata kunci: etosom, optimasi, fenilbutazon, transdermal